THE INFLUENCE OF EDUCATION AND JOB TRAINING ON EMPLOYEES' WORK PRODUCTIVITY PT. KELOLA OBONK KULINER INDONESIA IN INDONESIA - Suprobo, Dewi Larasati; Sutarno , Sutarno (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Kelola Obonk Kuliner Indonesia is a company operating in the food and beverage sector which oversees 8 outlet branches, namely 5 Obonk Steak and Ribs outlets branches located in Solo, Bali, Batam and Jakarta as well as 3 Bebek Haji Slamet By Obonk outlet branches located in Jakarta and Cirebon. This research aims to analyze the significance of the influence of education and job training on the work productivity of employees PT. Kelola Obonk Kuliner Indonesia in Indonesia. The type of data used in this research is quantitative data. The data sources used are primary data and secondary data. The population of this research is employees of PT. Kelola Obonk Kuliner Indonesia in Indonesia. The sampling technique used cluster random sampling with a sample size of 54 respondents. Data collection was carried out by distributing questionnaires using google form. The data analysis method in this research is multiple linear regression analysis using SPSS as a data processing tool. The research results show that education and job training have a significant effect on the work productivity of employees in the PT. Kelola Obonk Kuliner Indonesia in Indonesia. The R2 value is 41.8%, meaning that the work productivity of employees in the PT. Kelola Obonk Kuliner Indonesia can be explained by education and work training variables, while the remaining 58.2% means employee work productivity is explained by other variables, such as work motivation, work experience, work leadership, work discipline, work ethics, work environment, workload and so on which were not examined in this research.